2020
DOI: 10.1590/s0004-2803.202000000-73
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Stroop Encephalapp for Covert Hepatic Encephalopathy Screening in Cirrhotic Patients in Southern Brazil

Abstract: BACKGROUND: Covert hepatic encephalopathy (CHE) is difficult to detect due to the lack of easily applicable screening tools. The Stroop EncephalApp is a smartphone application already validated for CHE screening. However, its applicability to the Brazilian population is not known. OBJECTIVE: To estimate the prevalence of CHE and evaluate the use of Stroop EncephalApp in a cirrhotic population in Brazil. METHODS: In this cross-sectional study, we evaluated 99 patients previously diagnosed with liver cirrho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…O TRAT-C busca orientar o melhor esquema terapêutico para portadores de hepatite C (Pessoa et al, 2021). Já o Stroop EncephalApp visa o diagnóstico e avaliação de encefalopatia hepática mínima em pacientes cirróticos (Machado Júnior et al, 2020).…”
Section: Resultsunclassified
“…O TRAT-C busca orientar o melhor esquema terapêutico para portadores de hepatite C (Pessoa et al, 2021). Já o Stroop EncephalApp visa o diagnóstico e avaliação de encefalopatia hepática mínima em pacientes cirróticos (Machado Júnior et al, 2020).…”
Section: Resultsunclassified
“…Bajaj et al confirmed its external validity, face validity, and test-retest reliability [34]. EncephalApp_Stroop has been validated in Brazil, China and Korea, and was further expanded in the USA [31,33,35,36].…”
Section: Encephalapp_stroopmentioning
confidence: 95%